PENGEMBANGAN E-BOOK ACITUM (AKU CINTA TUMBUHAN) UNTUK MENGENALKAN BAGIAN DAN FUNGSI TUMBUHAN KEPADA SISWA KELAS IV DI SEKOLAH DASAR - Neliana; Ali Ismail; Regina Lichteria Panjaitan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Integrated learning media with technology is believed to be an effective alternative for teachers in supporting students' learning process. Currently, students need interesting digital teaching materials that support the learning process. This study aims to: 1) Determine the design and development of the ACITUM e-book (I Love Plants) to introduce plant parts and functions to fourth grade students in Elementary Schools. 2) Determine the results of the implementation of the development of the ACITUM e-book (I Love Plants) to introduce plant parts and functions to fourth grade students in Elementary Schools. The research method used in this study is Research and Development (R&D). This study uses the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The suitability aspect of the ACITUM e-book trial is in the very Valid category with a material feasibility percentage of 93% and a media feasibility percentage of 94%. The average SUS score for using the ACITUM e-book is 91.25, ranked A, with the Best Imaginable category, the ACITUM e-book is in an acceptable condition, and the interpretation results of the Net Promoter Score (NPS) show the Promoter level. The results of interviews with students showed that the ACITUM e-book was considered very helpful, interesting, and enjoyable for students in learning science materials, especially about the parts and functions of plants.